A 5-Year Follow-Up of Study Patients With Asymptomatic Iron-Deficiency Anemia Using a Nurse-Led Pathway. (November 2016) - Townsend, Sarah Ann; Cheung, Danny; Horne, Elaine; Ransford, Rupert
Abstract : A protocol-driven, systematic pathway was developed to allow rapid and coordinated investigation of patients with iron-deficiency anemia (IDA) in a nurse-delivered outpatient setting. The study objective was to assess the safety and efficacy of the pathway by 5-year outcome data for the exclusion of gastrointestinal (GI) malignancy. This is a 5-year follow-up study of 122 patients entered onto the pathway with negative initial upper and lower GI investigations. The study was conducted at Hereford County Hospital NHS Trust (a district general hospital serving 220, 00 people). Clinical outcomes of patients at 5 years and service efficiency at detecting relevant pathology were observed. A total of 272 patients were investigated through the pathway, and in 150 patients a GI cause for IDA was found. We established the outcome in 97% of the 122 patients with normal GI investigation at 5 years after their initial investigation. Of the 118 patients followed up, 92 patients were alive and well and 26 had died or developed malignancy. With the exception of diabetes (odds ratio 0.24; 95% confidence interval [0.1, 0.8]; p = .02), no features were found to be a significant risk factor for poor prognosis, including age, gender, hemoglobin level, anemia at 3 months, or other comorbidities. Three patients developed colonic malignancy; two patients had diverticular disease at barium enema and presented 4 years later with colorectal cancer. One patient declined lower GI investigation and presented with metastatic colon cancer on computed tomography scan at 1 year. No other GI cancers were diagnosed. Our nurse-delivered, protocol-driven pathway is a highly effective and safe system for the exclusion of GI cancer within 5 years of follow-up.